μ2: Using Mutation Analysis to Guide Mutation-Based Fuzzing - Laybourn, Isabella (2022 IEEE/ACM 44th International Conference on Software Engineering: Companion Proceedings (ICSE-Companion), 2022)
Coverage-guided fuzzing is a popular tool for finding bugs. This paper introduces μ 2 , a strategy for extending coverage-guided fuzzing with mutation analysis, which previous work has found to be better correlated with test effectiveness than code coverage. μ 2 was implemented in Java using the JQF framework and the default mutations used by PIT. Initial evaluation shows increased performance when using μ 2 as compared to coverage-guided fuzzing.